High‐Performance Flexible Nanostructured Silicon Solar Modules with Plasmonically Engineered Upconversion Medium. Issue 21 (3rd August 2015) - Lee, Sung‐Min; Li, Weigu; Dhar, Purnim; Malyk, Sergey; Wang, Yu; Lee, Wonmok; Benderskii, Alexander; Yoon, Jongseung
Abstract : A type of composite photovoltaic system that can improve the absorption of longer wavelength photons for ultrathin silicon solar cells is presented by synergistically exploiting spectral upconversion and plasmonic light manipulation under a reconfigurable platform where individual module components can be independently optimized and strategically combined by printing‐based deterministic materials assemblies. The ultrathin (≈8 μm) nanostructured silicon solar cells are embedded in a thin polymeric medium containing NaYF4 :Yb 3+, Er 3+ nanocrystals, coated on a plasmonically engineered substrate that incorporates hybrid nanostructures of cylindrical nanoholes and truncated‐cone‐shaped nanoposts. Both excitation and emission processes of upconversion luminophores are significantly enhanced by combined effects of surface plasmon resonance to amplify the light intensity at the excitation wavelength as well as to facilitate the far‐field outcoupling at the emission wavelengths, respectively. The performance of the integrated solar module is improved by ≈13% compared to devices on a nanostructured plasmonic substrate without luminophores due to collective contributions from plasmonically enhanced spectral upconversion, together with effects of waveguiding and fluorescence of NaYF4 :Yb 3+, Er 3+ . Detailed studies on optical properties of engineered plasmonic nanostructures and device performance in both experiments and numerical modeling provide quantitative descriptions of the underlying physics and materials science, as well as optimal design rules for integrated photovoltaic systems. Abstract : Plasmonically enhanced upconverion luminescence is exploited to improve the collection efficiency of above‐bandgap, long‐wavelength photons in ultrathin nanostructured silicon solar microcells. A composite solar module integrated with plasmonic silver nanostructures and upconversion printing medium enables the performance enhancement of surface‐embedded 8 μm thick nanostructured silicon microcells by synergistic effects of plasmonically enhanced spectral upconversion, waveguiding, and fluorescence of upconversion nanocrystals.